Putting gender upfront in One Health AMR research and implementation strategies - Erica Westwood; Evelyn Baraké; Jyoti Joshi (CABI, 2024)
Abstract Despite a gendered approach being increasingly applied across global health challenges, this has been a notable oversight in antimicrobial resistance (AMR) research. Failing to consider the complexity of human behaviours and roles in healthcare, animal production, and environmental settings compromises programmatic effectiveness and sustainability, while risking entrenching or widening existing social disparities. Research demonstrates how gender norms influence health-related behaviours across various sectors, from accessing healthcare to livestock rearing, with strong implications for antimicrobial stewardship and zoonotic disease transmission. The sparse literature connecting and investigating gender, equity and AMR - especially in a One Health context - hampers our ability to comprehensively address this global issue. The responsibility is however shared. This commentary advocates for funders to propel the inclusion of gender and equity-focused perspectives in AMR research and to set expectations in research landscapes, thus fostering a more equitable global health landscape and strengthening strategies against AMR. We outline our rationale and recommendations for other funders to support an ecosystem in AMR that supports gender and equity as a common aspect of AMR research and not an exception. One Health impact statement While AMR is increasingly recognised as a One Health challenge encompassing humans, animals, plants and the environment, sector-specific and cross-sectoral solutions needed to address AMR too often lack the multidisciplinary approach needed for a holistic response to this challenge. To date, AMR research has been largely biomedical, with limited social investigation including on gender and its interplay with factors that drive AMR in different settings such as healthcare, community or farm settings. Intentionally integrating gender analysis that informs AMR research design and implementation across sectors, including with supportive research funding opportunities, will help build the evidence base on how research projects and public programs should integrate and address gender disparities in AMR across the One Health spectrum. This is needed to ensure contextually relevant gender-informed solutions with sustainable impact.